Circulating Extracellular Vesicles in Gynecological Tumors: Realities and Challenges - Herrero, Carolina; Abal, Miguel; Muinelo-Romay, Laura (Frontiers in Oncology, 2020)
Although liquid biopsy can be considered a reality for the clinical management of some cancers, such as lung or colorectal cancer, it remains a promising field in gynecological tumors. In particular, circulating extracellular vesicles (cEVs) secreted by tumor cells represent a scarcely explored type of liquid biopsy in gynecological tumors. Importantly, these vesicles are responsible for key steps in tumor development and dissemination and are recognized as major players in cell-to-cell communication between the tumor and the microenvironment. However, limited work has been reported about the biologic effects and clinical value of EVs in gynecological tumors. Therefore, here we review the promising but already relatively limited data on the role of circulating EVs in promoting gynecological tumor spread and also their value as non-invasive biomarkers to improve the management of these type of tumors.